Resource scheduling of workflow multi-instance migration based on the shuffled leapfrog algorithm - Mingshun Yang; Xinqin Gao; Yuan Cao; Yong Liu; Yang Li (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: When the workflow changed, resource scheduling optimization in the process of the current running instance migration has become a hot issue in current workflow flexible research; purpose of the article is to investigate the resource scheduling problem of workflow multi-instance migration. Design/methodology/approach: The time and cost relationships between activities and resources in workflow instance migration process are analyzed and a resource scheduling optimization model in the process of workflow instance migration is set up; Research is performed on resource scheduling optimization in workflow multi-instance migration, leapfrog algorithm is adopted to obtain the optimal resource scheduling scheme. An example is given to verify the validity of the model and the algorithm. Findings: Under the constraints of resource cost and quantity, an optimal resource scheduling scheme for workflow migration is found, ensuring a minimal running time and optimal cost. Originality/value: A mathematical model for resource scheduling of workflow multi-instance migration is built and the shuffled leapfrog algorithm is designed to solve the model.
Keywords: 650; multi-instance migration; resource scheduling; leapfrog algorithm